DEVELOPMENT OF THE CLASSICAL CONCEPTION OF TEACHER RE FLECTED IN THE WORKS BY MAGDALENA KARČIAUSKIENĖ - Žemgulienė, Aušra; Montvilaitė, Sigita (Acta Paedagogica Vilnensia, 2009)
The article aims to show how the works by professor Magdalena Karčiauskienė reveal the development of classical conception of a teacher in Lithuania. The origins of this conception and the problems that occurred during its formation in the second half of the 19th century are discussed, the classical nature of this conception in the first half of the 20th century is analysed and the relevance of it is emphasised. In the first half of the 20th century the professional duty of a teacher was perceived as a civic obligation or public order which was particularly obvious: to restore the national school. The answer to the question what kind of teacher was capable of and had to fulfil these obligations is found through the analysis of the research papers by prof. M. Karčiauskienė and in her professional insights and references to the studied literature sources. The analysed studies highlight the conception of a teacher who demonstrates mature culture, civic awareness, integrity between spirit and moral, who is of high intelligence and has undergone high quality professional training.
Keywords: teacher; classical conception of a teacher; development of education